Continual distribution for the Bryan – Pidduck equation - Gordevskyy, V. D.; Hukalov , O. O. (Ukrains’kyi Matematychnyi Zhurnal, 2020)
UDC 533.72 For a nonlinear kinetic Boltzmann equation, in the case of a rough spheres model, we construct an approximate solution in the form of a continual distribution with the global Maxwellians. We also obtain the sufficient conditions on the coefficient functions and the hydrodynamic parameters, which are included in the distribution and make considered error arbitrarily small.